CO2 electroreduction favors carbon isotope 12C over 13C and facilitates isotope separation - Magda H. Barecka; Mikhail K. Kovalev; Marsha Zakir Muhamad; Hangjuan Ren; Joel W. Ager; Alexei A. Lapkin (iScience, 2023)
Summary: We discovered that CO2 electroreduction strongly favors the conversion of the dominant isotope of carbon (12C) and discriminates against the less abundant, stable carbon 13C isotope. Both absorption of CO2 in the alkaline electrolyte and CO2 electrochemical reduction favor the lighter isotopologue. As a result, the stream of unreacted CO2 leaving the electrolyzer has an increased 13C content, and the depletion of 13C in the product is several times greater than that of photosynthesis. Using a natural abundance feed, we demonstrate enriching of the 13C fraction to ∼1.3% (i.e., +18%) in a single-pass reactor and propose a scalable and economically attractive process to yield isotopes of a commercial purity. Our finding opens pathways to both cheaper and less energy-intensive production of stable isotopes (13C, 15N) essential to the healthcare and chemistry research, and to an economically viable, disruptive application of electrolysis technologies developed in the context of sustainability transition.